Clinical and Diagnostic Imaging Features of Brain Herniation in Dogs and Cats. (12th September 2016) - Lewis, M.J.; Olby, N.J.; Early, P.J.; Mariani, C.L.; Muñana, K.R.; Seiler, G.S.; Griffith, E.H.
Abstract : Background: Quantification of brain herniation on MRI and its immediate clinical implications are poorly described. Objectives: Define the normal position of caudal fossa structures on brain MRIs in dogs and cats utilizing morphometry, compare this to dogs and cats with caudal transtentorial herniation (CTH), foramen magnum herniation (FMH) or both identified on MRI, and investigate associations between herniation severity, clinical signs, and 24‐hour outcome. Animals: Ninety‐two controls (66 dogs, 26 cats), 119 cases with herniation (88 dogs, 31 cats). Methods: Retrospective case series. The MRI database was searched for controls with normal brain anatomy and cases with brain herniation. Morphometry in controls established TTX (transtentorial to rostroventral cerebellum) to quantify CTH and FMX (caudoventral cerebellum to foramen magnum) to quantify FMH. Measurements were compared between cases and controls. Correlations with specific clinical variables and outcome were investigated. Results: Measurements in medium/large control dogs versus small dog and cat controls were significantly different ( P < .001, TTX: −0.46, −0.305, −0.3, FMX: 0.695, 0.27, 0.25, respectively). 119/1564 (7.6%) cases that underwent brain imaging had brain herniation. TTX and FMX were significantly different between controls and cases with CTH or FMH ( P < .001). 67/89 (75%) cases with supratentorial lesions had no signs directly attributable to herniation. 71/119 (60%) had a normal anesthetic recovery. TTX was significantly associated with 24‐hour survival ( P < .001). Conclusions and clinical importance: Brain herniation can be quantified on MRI. Clinical signs directly attributable to brain herniation commonly are absent, and more severe CTH based on TTX is associated with a worse short‐term outcome.